2019
DOI: 10.3390/cells8080803
|View full text |Cite
|
Sign up to set email alerts
|

Role and Therapeutic Targeting of the PI3K/Akt/mTOR Signaling Pathway in Skin Cancer: A Review of Current Status and Future Trends on Natural and Synthetic Agents Therapy

Abstract: The mammalian or mechanistic target of rapamycin (mTOR) and associated phosphatidyl-inositiol 3-kinase (PI3K)/protein kinase B (Akt) pathways regulate cell growth, differentiation, migration, and survival, as well as angiogenesis and metabolism. Dysregulation of these pathways is frequently associated with genetic/epigenetic alterations and predicts poor treatment outcomes in a variety of human cancers including cutaneous malignancies like melanoma and non-melanoma skin cancers. Recently, the enhanced understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
130
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 203 publications
2
130
0
Order By: Relevance
“…Short treatment of melanoma cells with BRAF inhibitors has led to either augmented EGFR protein level as the result of epigenetic regulation [104] or increased phosphorylation of the baseline EGFR [105]. In addition, EGFR was correlated with resistance to BRAF inhibitors [102,103] by contributing to activity of ERK1/2 and AKT through a physical interaction with urokinase type plasminogen activator receptor (uPAR) in melanoma cells [114,115]. Our study has shown that selected trametinib-resistant cells can adaptively use EGFR, thus providing a therapeutic window for EGFR inhibition as a complementary treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…Short treatment of melanoma cells with BRAF inhibitors has led to either augmented EGFR protein level as the result of epigenetic regulation [104] or increased phosphorylation of the baseline EGFR [105]. In addition, EGFR was correlated with resistance to BRAF inhibitors [102,103] by contributing to activity of ERK1/2 and AKT through a physical interaction with urokinase type plasminogen activator receptor (uPAR) in melanoma cells [114,115]. Our study has shown that selected trametinib-resistant cells can adaptively use EGFR, thus providing a therapeutic window for EGFR inhibition as a complementary treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT/mTOR pathway is one of the most frequently activated signaling pathways in cancers and is responsible for tumor development, cellular metastasis, and proliferation (Polivka and Janku, 2014;Zhang et al, 2017;Chamcheu et al, 2019). In particular, the PI3K/AKT/mTOR pathway has attracted extensive attention as the modulator of autophagy (Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data presented in this study, it is difficult to propose a mechanism that can explain the said multiple effects on several mitochondrial processes. Considering the central role of Ca 2+ in regulating apoptosis and thereby the survival and therapy resistance of cancer cells [ 70 ], it is a limitation of this study that it cannot account for DEA’s effect on intracellular calcium.…”
Section: Discussionmentioning
confidence: 99%